Exploring University Students’ Willingness to Communicate and Unwillingness to Communicate in EFL - Fitri Susanti Ilyas (UIR Press, 2022)
This research investigates the contributive factors influencing students’ willingness to communicate (WTC) dan unwillingness to communicate (Un-WTC) in English as a foreign language in higher education in Indonesia. 10 first-year students which came from several non-English departments participated in the study and they represented the WTC and Un-WTC groups. Semi-structured observations and interviews were used to collect the data. The result reveals that there were two main factors contributing to their WTC and Un-WTC, namely individual dan external factors. The ideal L2 self, confidence, anxiety, and perceived communicative competence are among the individual factors, while teacher’s personality, types of activities and topics, classroom atmosphere subsumes to the external factors. These factors are interconnected and affect students’ WTC and Un-WTC in the classroom.